Impact of civil war on emotion recognition: the denial of sadness in Sierra Leone - Umilta', Maria Alessandra; Wood, Rachel; Loffredo, Francesca; Ravera, Roberto; Gallese, Vittorio (Frontiers in Psychology, 2013)
Studies of children with atypical emotional experience demonstrate that childhood exposure to high levels of hostility and threat biases emotion perception. This study investigates emotion processing, in former child soldiers and non-combatant civilians. All participants have experienced prolonged violence exposure during childhood. The study, carried out in Sierra Leone, aimed to examine the effects of exposure to and forced participation in acts of extreme violence on the emotion processing of young adults war survivors. A total of 76 young, male adults (38 former child soldier survivors and 38 civilian survivors) were tested in order to assess participants’ ability to identify four different facial emotion expressions from photographs and movies. Both groups were able to recognize facial expressions of emotion. However, despite their general ability to correctly identify facial emotions, participants showed a significant response bias in their recognition of sadness. Both former soldiers and civilians made more errors in identifying expressions of sadness than in the other three emotions and when mislabeling sadness participants most often described it as anger. Conversely, when making erroneous identifications of other emotions, participants were most likely to label the expressed emotion as sadness. In addition, while for three of the four emotions participants were better able to make a correct identification the greater the intensity of the expression, this pattern was not observed for sadness. During movies presentation the recognition of sadness was significantly worse for soldiers. While both former child soldiers and civilians were found to be able to identify facial emotions, a significant response bias in their attribution of negative emotions was observed. Such bias was particularly pronounced in former child soldiers. These findings point to a pervasive long-lasting effect of childhood exposure to violence on emotion processing in later life.